(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The facts show that agricultural production of small properties is unfeasible in the Third World. However, Nicaragua currently has an economic growth through agriculture. This is a traditional peasant society that has colonized their territory constantly moving the farming frontier. What existing territorial characteristics in Nicaragua allow in the xx1 century new agricultural frontier movements and in- tense internal migration? How has Nicaraguan agricultural space been since its founding as a nation to the present? Has the country been inserted in a process of re-peasantry? To try to answer these and other questions, in this paper, as back- ground, there is a historical account of the territorial characteristics of Nicaragua. Subsequently, the characteristics of agro are presented during Somocismo and the impact of agro-export model in the face of the country. In the second section the Sandinista policies and population changes caused by the war are analyzed. The third section analyzes the processes of internal colonization in the postwar peri- od, and finally the current characteristics of Nicaraguan agriculture, the policies pursued set forh by Daniel Ortega to turn back Nicaragua into a more peasant society, control the economic activity and finally, limit movements within is own agricultrual borders.